Errata Corrigenda and update for the “Synthesis of Brazilian Collembola: an update to the species list.” ABRANTES et al. (2010), Zootaxa, 2388: 1–22 - Abrantes, Eduardo Assis; Bellini, Bruno Cavalcante; Bernardo, Alessandra Do Nascimento; Fernandes, Liliane Henriques; de Mendonça, Maria Cleide; de Oliveira, Elisiana Pereira; Queiroz, Gabriel Costa; Sautter, Klaus Dieter; Da Silveira, Tatiana Cristina; Zeppelini, Douglas (Zootaxa, 2012)
We present in the following an Errata Corrigenda for Abrantes et al. (2010) Table 2 and general counting. Furthermore, we include all additional records for Brazilian Collembola during 2010 and 2011 as an update for the species list. The update was made following the same methodology and criteria as Culik and Zeppelini (2003), and Abrantes et al. (2010). All data will fit the same table marked differently to be recognized at glance. The references presented here are restricted to the citations concerning the update only; therefore the references presented in Culik and Zeppelini (2003), and Abrantes et al. (2010) will not be repeated.